FRI0301 DO PATIENTS AND PHYSICIANS AGREE ON THE DEFINITION OF REMISSION AND LOW DISEASE ACTIVITY IN AXIAL SPONDYLOARTHRITIS?. (2nd June 2020) - Valero, M.; Bachiller-Corral, J.; Blanco Cáceres, B. A.; Blázquez, M. Á.; Díaz-Miguel, C.; Garcia Villanueva, M. J.; Larena, C.; Morell Hita, J. L.; De la Puente Bujidos, C.; Rodriguez-García, A.; Vázquez Díaz, M.; Moltó, A.
Abstract : Background: Current recommendations for axial Spondyloarthritis (axSpA) include the treat-to-target concept and suggest that the ideal target should be remission or low disease activity (LDA). Also, the importance of a shared decision is highlighted. Unfortunately, the definition of remission is not consensual, and most of the definitions are difficult to evaluate in clinical practice Objectives: To propose an evaluation of remission by a single question to the patient, by comparing it to the different available definitions. To analyze the metric properties of the current definitions against patient's perception Methods: One-center cross-sectional study in a tertiary care hospital including consecutive patients with a diagnosis of axSpA (and fulfilling the ASAS criteria) were included between February to November 2019. Patient's perception of remission and LDA was evaluated by a single question. Physician's perception of remission and LDA was assessed identically. The level of agreement between patients' perception and the other available definitions was tested by the Prevalence and Bias adjusted Kappa (PABAK). The metric properties Sensitivity (S) and Specificity (Sp) of the available definitions (BASDAI cut-offs, ASDAS disease states, ASAS criteria for partial remission and patient acceptable symptom state), were tested against the patients perspective, as the gold standard. Results: A total of 105 axSpA patients were included. 63, 8% were males and 67, 6% had radiographic sacroiliitis (Table 1 ). 21% and 72% of them considered themselves in remission and LDA, respectively. Physician's perception was 45.7% and 81% for remission and LDA, respectively. The prevalence of the different definitions are shown in Figure 1 . The best agreement for patients's perception of remission was found with a BASDAI <2 + normal CRP (Table 2 ). This definition was also the most sensitive (S=72, 7%) and specific (Sp=83, 1%) when taking the patient's perception as a reference. Conclusion: In this real-life population, the evaluation of remission by the patient through a single question was shown to be feasible and to present an acceptable agreement with other definitions. References: [1]Gorlier C, et al. Ann Rheum Dis 2019;78(2):201-8. Acknowledgments: To Ansgar Seyfferth and Alfonso Muriel. To Carlos Sanchez-Piedra, Fernando Alonso and Mercedes Guerra from Sociedad Española de Reumatología, Research Unit. Disclosure of Interests: Marta Valero Grant/research support from: Novartis, Pfizer, Abvie, Speakers bureau: Novartis, Celgene, Javier Bachiller-Corral: None declared, Boris Anthony Blanco Cáceres: None declared, M. Ángeles Blázquez: None declared, Consuelo Díaz-Miguel: None declared, Maria Jesus Garcia Villanueva: None declared, Carmen Larena: None declared, Jose Luis Morell Hita: None declared, Carlos De la Puente Bujidos: None declared, Ana Rodriguez-García: None declared, Mónica Vázquez Díaz: None declared, Anna Moltó Grant/research support from: Pfizer, UCB, Consultant of: Abbvie, BMS, MSD, Novartis, Pfizer, UCB